SEVERE MARROW APLASIA SECONDARY TO CARBIMAZOLE - Ishak, Nur Adani; Katiman, Elliyyin; Aziz, Hazwani (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND One of the adverse effects of thionamide therapy for Graves’ disease is agranulocytosis. Generally, agranulocytosis recovers spontaneously after withdrawal of thionamide or with short course of granulocyte colony-stimulating factor (G-CSF). CASE We report a case of Graves’ disease presenting with delayed recovery of severe agranulocytosis after treatment with Carbimazole. A 26-year-old female diagnosed with Graves’ disease with high antibody titre presented with fever and sore throat after one month treatment with carbimazole 30 mg daily. She was treated as neutropenic sepsis with severe agranulocytosis. The baseline absolute neutrophil count was 0.01 x 109/L (3.929-7.147). She was started on G-CSF and broad-spectrum antibiotics including Piperacillin/Tazobactam and subsequently escalated to Meropenem. Her thyrotoxicosis was treated with lithium, prednisolone, and cholestyramine. Haematology team was also consulted in view of delayed recovery of severe aplasia and she was prepared for possible bone marrow transplant. The patient’s neutrophil counts recovered only after seven days of G-CSF treatment. It was later observed that she was not responding to treatment after two months of optimized dose of lithium, prednisolone, and cholestyramine. Hence, the patient was planned for semi-urgent total thyroidectomy. During admission for surgery, her fT4 level was 58.9 pmol/l (7.88 - 14.41). She required 3 cycles of plasma exchange and Lugol’s iodine prior to thyroidectomy as part of preoperative optimization. She underwent total thyroidectomy with fT4 level of 33.5 pmol/l. The surgery was successful with transient hypocalcaemia postoperatively. CONCLUSION This case showed a rare incident of delayed recovery of severe marrow aplasia secondary to Carbimazole. In view of resistance to second line thyrotoxicosis treatment, the patient underwent semi-urgent total thyroidectomy with plasma exchange prior to surgery.